Pendampingan Gerakan Literasi Sains (GLS) Di SDN Girimoyo 2 Malang - Yayuk, Erna; Kuncahyono, Kuncahyono; Restian, Arina (Publikasi Pendidikan, 2018)
Literacy of science is the knowledge and scientific ability to identify questions, acquire new knowledge, explain scientific phenomena, and take conclusions based on facts, understand the characteristics of science, awareness of how science and technology shapes the natural, intellectual and cultural environment, and the willingness to engage and care issues related to science. The National Research Council (2012) states that a series of required scientific competencies in science literacy reflects the view that science is an ensemble of common social and epistemic practice in all science, framing all competencies as action. The purpose of this assistance is to equip teachers in the implementation of the school literacy movement, especially the movement of science litersi. The activity method is divided into three stages including GLS workshop, GLS implementation, and Reflection Evaluation. Based results include mentoring the preparation of Science literacy programs by schools, Manual GLS implementation programs and examples of GLS class setting settings, and the establishment of classroom settings with a reading angle design in each class as a supporting element of science literacy.